The History of Architectural Development and Gradual Evolution of Sardobas in Central Asia (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article provides information on the historical architectural development of sardobas in Central Asia, their functional purposes, and architectural features. It also discusses the architectural and structural complexity of these hydro-technical constructions, as well as the stages of their artistic and aesthetic evolution.